Notions of family intersectional perspectives - Kohlman, Marla H.; Krieg, Dana B.; Dickerson, Bette J. (Advances in gender research, 2013)
Notions of Family: Intersectional Perspectives presents new and original research on gender and the institution of family featuring both quantitative and qualitative analyses. The objective of this volume is to present a framework for understanding the ways in which the salient identities of gender, class position, race, sexuality, and other demographic characteristics function simultaneously to produce the outcomes we observe in the lives of individuals as integral forces in the maintenance of family. While there is a large body of literature in each of these demographic areas of analysis and theory, only within the past decade have academics attempted to model and analyze the "simultaneity" of their functioning as one concerted force in our everyday lived experience. Moreover, there has been little directed focus on any particular institutional force in current textual discussions of intersectionality. We seek to begin the process of addressing this void in the academic literature with this edited volume on the family as a societal institution.